2010
DOI: 10.5424/sjar/201008s2-1343
|View full text |Cite
|
Sign up to set email alerts
|

Review. Deficit irrigation in fruit trees and vines in Spain

Abstract: Water has become the most precious of natural resources in many areas of Spain and, since agriculture is the major consumer of water, improvements in water use efficiency are increasingly sought. Regulated deficit irrigation (RDI) is an irrigation strategy based on applying only a fraction of the plant water requirements during certain periods of plant development. The paper reviews the available information on RDI strategies, in woody tree crops and vines based on studies by Spanish research groups. Both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
19

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(125 citation statements)
references
References 97 publications
3
97
0
19
Order By: Relevance
“…In Citrus sp. by contrast, the most successful period is during summer, after fruit drop (Ruiz-Sanchez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Citrus sp. by contrast, the most successful period is during summer, after fruit drop (Ruiz-Sanchez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…irrigating, fertilizing, spraying and pruning. The literature describes the stage II of fruit growth in medium-and late-maturing cultivars, and the postharvest period as the most suitable for reducing irrigation in peach trees (Ruiz-Sánchez et al, 2010); however, deficit irrigation strategies should be adjusted to limit water deficits during the exceedingly long postharvest period for early-maturing peach cultivars .…”
Section: Crop Load and Peach Tree Growthmentioning
confidence: 99%
“…The application of regulated deficit irrigation requires an accurate knowledge of the critical phenological periods during which the sensitivity of plants to water stress is maximal (Girona et al, 2005;Ruiz-Sánchez et al, 2010;Vera et al, 2013). However, the availability of carbohydrate resources also limits reproductive growth and, thus, it has been reported that carbohydrate distribution within the tree − fruit number and position (thinning), vegetative growth and tree configuration (pruning) − affect peach yield (DeJong, 1999;Naor et al, 1999;López et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Though, the response of trees to water stress may have distinct consequences according to the moment of application, the intensity of stress and its duration (Ruiz-Sánchez et al, 2010) and the use of the traditional methodologies led to high variability and uncertainties to provide an accurate water supply in time and quantities since tree water use results being a complex process integrating the effect of all these factors.…”
Section: Effect Of Water Deficit On Tree Physiologymentioning
confidence: 99%